2010
DOI: 10.1002/jssc.200900638
|View full text |Cite
|
Sign up to set email alerts
|

Determination of thermodynamic parameters in reversed phase chromatography for polyethylene glycols and their methyl ethers in different mobile phases

Abstract: The thermodynamic parameters (entropy and enthalpy change) and their increment per repeat unit have been determined in RP chromatography of PEG and its mono- and dimethyl ethers in different mobile phases. The different approaches for their determination and the problems related to the characteristic volumes (void volume, interstitial volume, pore volume) of the column are discussed. Very different dependences or the thermodynamic parameters were observed in aqueous mobile phases containing ACN, acetone, or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Such terminal effect on the thermodynamic parameters is also observed in IC of polymers. 81 Further study on this intriguing column retention mechanism will be performed in our group with the aim of developing a new methodological framework for macromolecular recognition and separation. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Such terminal effect on the thermodynamic parameters is also observed in IC of polymers. 81 Further study on this intriguing column retention mechanism will be performed in our group with the aim of developing a new methodological framework for macromolecular recognition and separation. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, normal-phase HPLC showed better resolution for high molecular weight PEG oligomers than RP-HPLC. 103 , 104 Cho et al confirmed this finding, stating that NP-HPLC with an amino-bonded silica stationary phase provided ease in analyzing high molecular mass PEG samples. 105 …”
Section: Characterizationmentioning
confidence: 83%
“…Furthermore, normal-phase HPLC showed better resolution for high molecular weight PEG oligomers than RP-HPLC. 103,104 Cho et al confirmed this finding, stating that NP-HPLC with an amino-bonded silica stationary phase provided ease in analyzing high molecular mass PEG samples. 105 Moreover, the temperature effect on the retention time was studied, and it showed that the separation of PEG polymers can be realized by using thermal gradients using an isocratic gradient; however, this was only verified for PEGs with MW < 2000 Da.…”
Section: Characterizationmentioning
confidence: 85%
See 1 more Smart Citation
“…As concerns analytical chromatography, also, the accurate determination of the MWD of PEGs is of interest, in particular for medium and large MWs. Analysis of PEGs by high-performance liquid chromatography (HPLC) has been studied using reversedphase (RP-HPLC) and normal phase (NP-HPLC) [3,[10][11][12][13][14][15][16][17][18][19][20]. Alternatively, supercritical fluid chromatography (SFC) can be applied [21,22].…”
Section: Introductionmentioning
confidence: 99%